VIDEO COMPANY PROFILE SEBAGAI STRATEGI PROMOSI POTOKITA SELF STUDIO - Jerricho Ivandro Ekklesia; Yunita Indinabila (DIGICOM : Jurnal Komunikasi dan Media, 2025)
The digital era has driven the emergence of the increasingly popular self-photo studio trend. ”Potokita Self Studio" is one of the studios that adopts the self-photo studio concept and offers diverse range of services. Despite its unique concept, the increasingly competitive photography market drives “Potokita Self Studio” to adopt more effective promotional strategies, one of which is the use of a company profile video as an informative and engaging promotional medium. This practice-based research aims to produce a company profile video as a promotional strategy for “Potokita Self Studio.” The production went through three stages: pre-production, production, and post-production, resulting in a 6-minute 29-second company profile video. The video is designed with a cinematic style, poetic voice-over narration, and aesthetically pleasing visuals, it presents the company profile, historical background and founding spirit, team dedication, information on services and products, organizational values, corporate culture, philosophy, business development, and the overall customer experience. The video was published on the “Potokita Self Studio” YouTube channel on July 21, 2025, and as of August 24, 2025, it had received 67 likes and 235 views. These early results demonstrate the potential of a company profile video to enhance digital brand awareness. Overall, a company profile video can serve as an effective and relevant promotional strategy that strengthens brand identity.